Early bone ingrowth of Cu-bearing CoCr scaffolds produced by selective laser melting: An in vitro and in vivo study - Yanjin Lu; Yuan Zhou; Xiongwei Liang; Xianzeng Zhang; Chengke Zhang; Min Zhu; Kanglai Tang; Jinxin Lin (Materials & Design, 2023)
In this study, the Co29Cr9W3Cu porous scaffolds with different unit cell types including octahedron (OCT), face-centered cubic (FCC), and hexahedron (HCP) were fabricated by selective laser melting, aiming to reduce the stress shielding effect and promote the early bone ingrowth. The effect of pore size and unit cell types on the compressive stress and elastic modulus were investigated, and regulating pore size led to the compressive stress and elastic modulus ranging from 3.7 to 467 MPa and from 2.6 to 36.3 GPa, respectively. The in vitro results demonstrated that the ability to support the osteogenesis and angiogenesis was for the most part similar between the FCC-65, OCT-65, and HCP-65 scaffolds (porosity of 65%). After implantation in goats for 12 weeks, the FCC-65, OCT-65, and HCP-65 scaffolds showed sufficient results for guiding bone ingrowth, indicating good biocompatibility and osteointegration; interestingly, the scaffold with OCT unit cell structure offered the strongest ability to accelerate bone mineralization compared with the FCC-65, HCP-65 scaffold, possibly due to mechanical-adapted properties. The study was expected to offer the possibility of the SLM-produced Co29Cr9W3Cu scaffold to achieve osseointegration by guiding early bone ingrowth into the bone contact porous surface of the ankle joint.